Seed banking of Polish endangered plants – the FlorNatur Project - Puchalski, Jerzy; Niemczyk, Maciej; Walerowski, Piotr; Podyma, Wiesław; Kapler, Adam (Biodiversity: Research and Conservation, 2015)
Among the 2750 species of the Polish vascular flora, about 500 species are threatened with extinction and 430 of them are strictly protected by national law. The FlorNatur project for the ex situ conservation of the most endangered species was started in 2009. The aim of the project is to collect seeds of 61 species from 161 sites in eastern Poland and store them in the Seed Bank of the Polish Academy of Sciences Botanical Garden - Center for Biological Diversity Conservation in Warsaw- Powsin. A complementary program is being carried out by the Forestry Gene Bank at Kostrzyca in western Poland. Their task is to collect 58 species from 129 natural sites in the western part of Poland. To date, seeds of 31 species from 56 populations have been collected, tested and stored in liquid nitrogen.